Something Is Changing in Viral Infant Bronchiolitis Approach - Bottau, Paolo; Liotti, Lucia; Laderchi, Eleonora; Palpacelli, Alessandra; Calamelli, Elisabetta; Colombo, Carlotta; Serra, Laura; Cazzato, Salvatore (Frontiers in Pediatrics, 2022)
Acute Viral Bronchiolitis is one of the leading causes of hospitalization in the first 12–24 months of life. International guidelines on the management of bronchiolitis broadly agree in recommending a minimal therapeutic approach, not recommending the use of bronchodilators. Guidelines, generally, consider bronchiolitis as a “unique disease” and this runs the risk of not administering therapy in some patients who could benefit from the use of bronchodilators, for instance, in those who will develop asthma later in their life and face first episode in the age of bronchiolitis. Today, there is growing evidence that bronchiolitis is not a single illness but can have different “endotypes” and “phenotypes,” based on age, personal or family history of atopy, etiology, and pathophysiological mechanism. There is evidence that some phenotypes of bronchiolitis are more strongly associated with asthma features and are linked to higher risk for asthma development. In these populations, possible use of bronchodilators might have a better impact. Age seems to be the main feature to suggest a good response to a bronchodilator-trial, because, among children > 6 months old with bronchiolitis, the presence of a subset of patients with virus-induced wheezing or the first episode of asthma is more likely. While waiting for new research to define the relationship between therapeutic options and different phenotypes, a bronchodilator-trial (using short-acting β2 agonists with metered-dose inhalers and valved holding chambers) seems appropriate in every child with bronchiolitis and age > 6 months.